The Implementation Of Inquiry-Based Learning In Teaching English at SMP Negeri 1 Gemolong In 2015/2016 Academic YearResearch Paper - Lestari, Endang; , Prof. Dr. Endang Fauziati, M.Hum; , Aryati Prasetyarini, S.Pd. M.Pd (2016)
ENDANG LESTARI. A 320120092. THE IMPLEMENTATION OF INQUIRYBASED LEARNING IN TEACHING ENGLISH AT SMP NEGERI 1 GEMOLONG IN 2015/2016 ACADEMIC YEAR. Research Paper. Muhammadiyah University of Surakarta. 2016. This is a naturalistic qualitative research which aims to describe and explain the implementation of Inquiry-based Learning in teaching English at SMP negeri 1 Gemolong consisting the component of teaching learning namely; learning objective, classroom procedure, classroom technique, the role of instructional material, teacher's role, students' role, media, assessment. The researcher used observation, interview and document in collecting the data. Based on the research findings, the researcher found the results as follows; 1) there are two kind of learning objectives, namely general learning objectives and specific learning objectives. 2) classroom procedure used exploration, elaboration, confirmation. 3) classroom techniques used in teaching English were problem solving, discussion, reading text, answering question, role playing, crazy story games, presentation. 4) the roles of instructional materials were as a reference source for learners on grammar, vocabulary, pronunciation; as a source of stimulation and ideas for classroom activities. 5) English teacher had roles as facilitator, manager, explainer, motivator. 6) students' roles were students learning from teacher, students as subject of learning, students as performer, students learn from other students. 7) media used in teaching English were video, drama, board, text. 8) assessment used by teacher were test and non-test, test was divided into daily test, mid test, and final test. Non-test was divided into every skill in teaching learning process. Keywords: inquiry-based learning, teaching English